Asymmetric Information and Monetary Policy in Common Currency Areas - Laura Bottazzi; Paolo Manasse (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2002)
In a Common Currency Area (CCA) the Common Central Bank sets a uniform rate of inflation across countries, taking into account the area's economic conditions. Suppose that countries in recession favor a more expansionary policy than countries in expansion, a conflict of interest between members arises when national business cycles are not fully syncronized. If governments of member countries have an informational advantage over the state of their domestic economy, such conflict may create an adverse selection problem: national authorities overemphasize their shocks, in order to shape the common policy towards their needs. This creates an inefficiency over and above the one-policy-fits-all cost discussed in the optimal currency area literature. In order to minimize this extra-burden of asymmetric information, monetary policy must over-react to large symmetric shocks and under-react to small asymmetric ones. The result is sub-optimal volatility of inflation.
Keywords: 330